2020
DOI: 10.34024/rnc.2020.v28.10247
|View full text |Cite
|
Sign up to set email alerts
|

Conhecimento e Utilização da CIF por Docentes Fisioterapeutas na Cidade de Teresina - PI

Abstract: INTRODUÇÃO: Em 2001 foi aprovado a Classificação Internacional de Funcionalidade, Incapacidade e Saúde com uma visão biopsicossocial e linguagem padronizada sendo assim diferente das demais, ela tem como objetivo auxiliar desde a avaliação até o tratamento do paciente abordando os aspectos biopsicossociais e funcionais, sendo o fisioterapeuta o profissional mais relacionado com os aspectos cinéticos funcionais dos seres humanos. OBJETIVO: Avaliar o conhecimento e utilização da classificação internacional de fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
1
0
0
1
Order By: Relevance
“…In terms of their own work process, 63.20% of the professors reported that they were unable to maintain the desired level of quality(Table 2).Participants in the present study were professors from graduate physical therapy courses at public and private higher education institutions distributed across the different regions of Brazil. Although the vast majority of these courses are offered at private HEIs, there was a balance between professors from both types of institutions in the study sample.Studies that characterize professors in Brazilian graduate physiotherapy programs are scarce, and as such, our aim was to understand the profile of the professionals currently working at HEIs in the country.Most of the participants were women, with similar findings reported by other authors [16][17][18]. Because this…”
supporting
confidence: 88%
“…In terms of their own work process, 63.20% of the professors reported that they were unable to maintain the desired level of quality(Table 2).Participants in the present study were professors from graduate physical therapy courses at public and private higher education institutions distributed across the different regions of Brazil. Although the vast majority of these courses are offered at private HEIs, there was a balance between professors from both types of institutions in the study sample.Studies that characterize professors in Brazilian graduate physiotherapy programs are scarce, and as such, our aim was to understand the profile of the professionals currently working at HEIs in the country.Most of the participants were women, with similar findings reported by other authors [16][17][18]. Because this…”
supporting
confidence: 88%
“…(Castro, Pinto & Almeida, 2015) No presente estudo foi avaliado o nível de conhecimento da CIF pelos fisioterapeutas atuantes no estado de Pernambuco, sendo observado que a grande maioria (94,5%) possui conhecimento regular desta, adquirido principalmente no meio acadêmico. Santos et al (2020) em um estudo realizado com fisioterapeutas da cidade de Teresina -PI, também observou que grande parte dos profissionais (90,32%) tinham conhecimento sobre a CIF e que o primeiro contato foi através da graduação. Com isso podemos destacar que estes achados sugerem que as instituições de ensino de graduação e especialização estão seguindo as recomendações do COFFITO/CREFITO que recomenda às instituições de ensino superior a trazer para os acadêmicos o conhecimento sobre a CIF.…”
Section: Discussionunclassified